pH-Sensitive Peptide Hydrogels as a Combination Drug Delivery System for Cancer Treatment - Liu, Yuanfen (2022)
Conventional antitumor chemotherapeutics generally have shortcomings in terms of dissolubility, selectivity and drug action time, and it has been difficult to achieve high antitumor efficacy with single-drug therapy. At present, combination therapy with two or more drugs is widely used in the treatment of cancer, but a shortcoming is that the drugs do not reach the target at the same time, resulting in a reduction in efficacy. Therefore, it is necessary to design a carrier that can release two drugs at the same site. We designed an injectable pH-responsive OE peptide hydrogel as a carrier material for the antitumor drugs gemcitabine (GEM) and paclitaxel (PTX) that can release drugs at the tumor site simultaneously to achieve the antitumor effect. After determining the optimal gelation concentration of the OE polypeptide, we conducted an in vitro release study to prove its pH sensitivity. The release of PTX from the OE hydrogel in the medium at pH 5.8 and pH 7.4 was 96.90% and 38.98% in 7 days. The release of GEM from the OE hydrogel in media with pH of 5.8 and 7.4 was 99.99% and 99.63% in 3 days. Transmission electron microscopy (TEM) and circular dichroism (CD) experiments were used to observe the microstructure of the peptides. The circular dichroism of OE showed a single negative peak shape when under neutral conditions, indicating a β-folded structure, while under acidic conditions, it presented characteristics of a random coil. Rheological experiments were used to investigate the mechanical strength of this peptide hydrogel. Furthermore, the treatment effect of the drug-loaded peptide hydrogel was demonstrated through in vitro and in vivo experiments. The results show that the peptide hydrogels have different structures at different pH values and are highly sensitive to pH. They can reach the tumor site by injection and are induced by the tumor microenvironment to release antitumor drugs slowly and continuously. This biologically functional material has a promising future in drug delivery for combination drugs.